Design of a Web-Based Wedding Organizer Service System Application for CV. Ruang Event in Bandar Lampung Using the Waterfall Method - Lalo, Oktavianus; Karo-Karo, Panser; Faizah, NM (Yayasan Kawanad, 2025)
Marriage represents a sacred milestone requiring meticulous preparation from every couple. CV. Ruang Event, a wedding organizer service provider in Bandar Lampung, faces significant operational challenges due to outdated manual systems. Primary issues include unstructured client documentation, fragmented transaction data storage, and time-consuming report generation prone to human error. These conditions result in data inaccuracy, delayed information retrieval, and deteriorating customer service quality. The research aims to develop a web-based information system to optimize CV. Ruang Event's business processes using the Waterfall methodology. Development phases encompass system requirement analysis, database and interface design, implementation using PHP and MySQL, and functional testing. The research produces a web application facilitating online wedding organizer package bookings, event schedule management, digital payment systems, and automated reporting. Core features include package catalogs (Silver, Gold, Diamond/Platinum) priced from IDR 3,500,000 to IDR 38,000,000, booking calendars, payment confirmations, and administrative dashboards. Testing demonstrates 60% operational efficiency improvement, 85% reduction in recording errors, and enhanced customer satisfaction through improved information accessibility. The system successfully integrates entire business processes from booking to reporting, delivering a complete solution for wedding organizer service digitalization.